Health Impact of Community-Based Water Treatment Systems in Honduras. (25th December 2011) - Deal, Jeffery
Abstract : This paper provides a followup on a previous report in this journal on the health impact of providing access to water treatment and flush toilets to region of Honduras. Significant reductions were found in the one-year incidence of positive test results for the three protozoan species tested. This finding combined with the previously reported ethnographic and medical chart review data provides compelling evidence that such interventions significantly reduce the disease load from waterborne pathogens within this population. Furthermore, the finding that initial results are significantly different, even in the initial round of testing, if individuals who are not followed up are eliminated from the analysis has profound methodological implications which warrant further investigation and demonstrates the need for precise definitions of community in future studies.